A Cost-Effectiveness Analysis: First-Line Avelumab Plus Axitinib Versus Sunitinib for Advanced Renal-Cell Carcinoma - Lu, Peiyao; Liang, Weiting; Li, Jiahao; Hong, Yanming; Chen, Zhuojia; Liu, Tao; Dong, Pei; Huang, Hongbing; Zhang, Tiantian; Jiang, Jie (Frontiers in Pharmacology, 2020)
Background: Compared with the standard of care with sunitinib, avelumab plus axitinib can increase progression-free survival in the first-line of advanced renal cell carcinoma (RCC), but the economic effect of the treatment is unknown. The purpose of the research was to evaluate the cost-effectiveness of the avelumab plus axitinib vs sunitinib in first-line treatment for advanced RCC from the US payer perspective. Methods: A Markov model was developed to evaluate the economic and health outcomes of avelumab plus axitinib vs sunitinib in the first-line setting for advanced RCC. The clinical data were obtained from the JAVELIN Renal 101 Clinical Trials. Deterministic and probabilistic sensitivity analyses were performed to assess uncertainty in the model. Health outcomes were measured in quality-adjusted life-years (QALYs). Results: The incremental cost-effectiveness ratio (ICER) of avelumab plus axitinib compared with sunitinib was＄565,232 per QALY, the costs were＄884,626 and＄669,838, QALYs were 3.67 and 3.29, respectively. Sensitivity analysis demonstrated that differences in utilities in PFS and after progression were the most influential factors within the model. When avelumab was at 30% of the full price or axitinib was at 40% of the full price, avelumab and axitinib were approved to be cost-effective if the WTP threshold was $150,000 per QALY. The subgroup analysis showed the ICER of avelumab plus axitinib compared with sunitinib for the patients with PD-L1–positive tumors was ＄588,105. Conclusion: Avelumab plus axitinib in the first-line treatment was not cost-effective in comparison with sunitinib when the threshold of willingness to pay (WTP) was $150,000 per QALY.